Antihistaminics, local anesthetics, and other amines as antiviral agents. - Miller, D K (1981)
A number of lipophilic amines of diverse chemical structure, including antihistaminics, local anesthetics, and chloroquine, were found to exhibit similar kinetics in inhibiting the infection of BHK cells by vesicular stomatitis virus. The inhibition occurred prior to both primary and secondary RNA transcription but following transfer from the cell surface to an intracellular site, presumed to be the lysosomes. A similar inhibition, by these agents, of infection by Sendai, influenza strain WSN, and Semliki Forest viruses suggested a lysosomal involvement in infection by these viruses as well.